Tutoring and preceptory in multiprofessional residence programs in basic care: a necessary dialogue (Research, Society and Development, 2020)
This study aimed to analyze the perception of Tutors, Preceptors and Residents of Multi-Professional Residency Programs in Primary Health Care (PRMS-AB) developed in Southern Brazil, as participants in this type of formation. Descriptive and qualitative study conducted from May to September 2016, by electronic questionnaire (closed and open questions) for Tutors, Preceptors and Residents, analyzed by the technique of Content Analysis. 23 Tutors, 14 Preceptors and 22 Residents from six Higher Education Institutions participated. The professional qualification of 84.2% of the Tutors was in Collective Health, Public Health or Higher Education; 92.9% of Preceptors had at least one specialization in these areas. Tutors and Preceptors attributed the lack of time and fragility of the teaching-service relationship as difficulties. For Residents, the lack of core Preceptor or the overload of Nurse Preceptor weakens training. Tutoring positively influenced the teaching exercise in undergraduate; For Preceptors, PRMS-AB enabled changes in the work process. Residents rated AB as an appropriate field for core activities. According to those involved, PRMS-AB are potent to (trans) train health professionals and services.